PERENCANAAN BISNIS SISTEM INFORMASI PERCETAKAN ONLINE BERBASIS APLIKASI WEB - Laser Narindro; Hendra Maya Topani (Jurnal Informatika, 2017)
The evolution of technology of information right now can affects human lifestyle so each individuals forced to follow the evolution so they are not left behind from the technology of information. Technology and information system this time already become a requirement and information resource for the users. This time, every fans of music, especially the fans of angklung instrumental, even for a beginner or a professionals hoping that’s someday there will be a development for an application of angklung instrumental based on android who can complete the needed of angklung instrumental users as a tools to education and entertainment who can play anywhere and anytime through a hardware called smartphone with android’s platform. This angklung application production is using an application called java eclipse, so when using this angklung application the users can get the details information, interactive with good and can conserve this traditional angklung instrumental.